Aortic elasticity and carotid intima-media thickness in children with mitral valve prolapse - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2018)
Aim: We aimed to study the dimensions, systolic and diastolic functions of the left ventricle; dimensions and elasticity of the aorta; and carotid intima-media thickness and flow-mediated dilatation of the brachial artery in mitral valve prolapse. Methods: The study group consisted of 43 patients (mean age = 13.3 +/- 3.9) and 42 healthy children (mean age = 12.9 +/- 3.4). Left ventricular end-diastolic, end-systolic, left atrial diameters, interventricular septum, and left ventricular posterior wall thickness were measured. Ejection and shortening fractions were calculated by M-mode. Measurements were adjusted to the body surface area. Mitral annulus, and systolic and diastolic diameters of the aortic annulus and aorta at each level were obtained; z-scores, aortic strain, distensibility, stiffness index were calculated. Carotid intima-media thickness and flow-mediated dilatation were studied. Patients were classified as classical/non-classical mitral valve prolapse and younger/older patients. Results: Left ventricular end-systolic, end-diastolic, and left atrial diameters (p = 0.009, p = 0.024, p = 0.001) and aortic z-scores at annulus, sinus valsalva, and sinotubuler junction were larger (p = 0.008, p = 0.003, p = 0.002, respectively) in the mitral valve prolapse group. Aortic strain and distensibility increased and stiffness decreased at the ascending aorta in the patient group (p = 0.012, 0.020, p = 0.019, respectively). Classical mitral valve prolapse had lower strain and distensibility and higher stiffness of the aorta at sinus valsalva level (p = 0.010, 0.027, 0.004, respectively). Carotid intima-media thickness was thinner in the patient group, especially in the non-classical mitral valve prolapse group (p = 0.037). Flow-mediated dilatation did not differ among the groups. Conclusion: Mitral valve prolapse is a systemic disease of the connective tissue causing enlarged cardiac chambers and increased elasticity of the aorta. Decreased carotid intima-media thickness in this group may indicate low atherosclerosis risk.
Keywords: Mitral valve prolapse; children; aortic elasticity; carotid intima-media thickness; MARFAN-SYNDROME; CONNECTIVE-TISSUE; ECHOCARDIOGRAPHIC FEATURES; GENERAL-POPULATION; FIBRILLIN-1 GENE; ASCENDING AORTA; HEART-DISEASE; ASSOCIATION; RISK; STIFFNESS